Harmonization of Islamic Law in National Legal System: A Comparative Study Between Indonesia Law and Malaysian Law - Barlinti, Yeni Salma (UI Scholars Hub, 2011)
This artcile compares Indonesia legal system. The government legalized Islamic Law in national legislations, which are in effect for Muslim People. To facilitate dispute settlement, there is a relgious court to solve Islamic dispute based on Islamic Law. The Existance of Islamic law in Indonesia and Malaysia has similarity and differentiation. The similarties among others are: the Muslim-majority in both countries pushes the government to put Islamic law into force, Islamic law must be written into consitution or legislation. It is needed to have legal basis when performing Islamic law, the existence of relgious court is very important in dispute settlement related to Islamic Law. The influence of western legal system is very strong in national legal system. Neverheless, the western legal system differs substantially from Islamic legal system, and Islamic law was implemented limitedly based upon western legislation. It was limited to fiamily law. While the differentitaiton are: the way of implementation of western legal system into national legal systemn and the form of legislation. Indonesia has one legislation, which is in effect to all of Indonesia people. On the contrary, Malaysia has many enactments, which are different from one to another in each negeri.